Combined ultrasound and isotope scanning is more informative in the diagnosis of congenital hypothyroidism than single scanning. Issue 12 (24th July 2006) - Perry, R J; Maroo, S; Maclennan, A C; Jones, J H; Donaldson, M D C
Abstract : Background: Thyroid imaging is helpful in confirming the diagnosis of congenital hypothyroidism and in establishing the aetiology. Although isotope scanning is the standard method of imaging, ultrasound assessment may be complementary. Aim: To determine the strengths and weaknesses of thyroid ultrasound and isotope scanning in neonates with thyroid stimulating hormone (TSH) elevation. Methods: Babies from the West of Scotland with raised capillary TSH (>15 mU/l) on neonatal screening between January 1999 and 2004 were recruited. Thyroid dimensions were measured using ultrasonography, and volumes were calculated. Isotope scanning was carried out with a pinhole collimator after an intravenous injection of 99m-technetium pertechnetate. Results: 40 infants (29 female) underwent scanning at a median of 17 days (range 12 days to 15 months). The final diagnosis was athyreosis (n = 11), ectopia (n = 12), hypoplasia (n = 8; 3 cases of hemi-agenesis), dyshormonogenesis (n = 5), transient hypothyroidism (n = 2), transient hyperthyrotropinaemia (n = 1) and uncertain status with gland in situ (n = 1). 6 infants had discordant scans with no isotope uptake but visualisation of thyroid tissue on ultrasound. This was attributed to TSH suppression from thyroxine (n = 3); maternal blocking antibodies (n = 1); cystic degeneration of the thyroid (n = 1); and possible TSH receptor defect (n = 1). Conclusions: Isotope scanning was superior to ultrasound in the detection of ectopic tissue. However, ultrasound detected tissue that was not visualised on isotope scanning, and showed abnormalities of thyroid volume and morphology. We would therefore advocate dual scanning in newborns with TSH elevation as each modality provides different information.